(untitled) (Вісник: Міжнародні відносини, 2024)
Introduction. The information space of the People’s Republic of China has turned out to be the most difficult area of the information struggle. The peculiarities of its internal functioning, the absence of any Ukrainian media in China, and the influence of powerful Russian “partner” propagandists have posed difficult challenges and tasks for Ukrainians. For years, Russia has been pouring significant resources into shaping a positive image of the country and its leader for the Chinese consumer of information. In addition, China has been adopting Russian methods of conducting information warfare against Ukraine for more than a decade, especially during the period of full-scale Russian aggression, and has begun to actively use them in the international arena. Methods. The priorities of China’s state information policy are considered on the basis of systemic, structural-functional and comparative research methods, which allowed to reflect the practical experience of the Chinese political authorities in achieving goals in the external and internal spheres. Results. On the basis of the political analysis of the state information policy of the People’s Republic of China (PRC), the author proves the leading role of China’s political ideology in its formation in the context of the full-scale Russian-Ukrainian war and, as a result, the irreversible future change in the world order, which requires further adjustment of the current state of information cooperation between Ukraine and China. Conclusions. China’s international aspirations are realized with state support at the level of political decisions, executive structures, legislative support and directed influence on the society’s awareness of new opportunities of the information civilization. At the same time, China is actively studying the experience of Russia’s information warfare against Ukraine and its Western allies, willingly applying such methods as disinformation and the use of fakes, which have become Beijing’s chosen information weapon. Today, information cooperation between Ukraine and China is in its infancy: the Chinese population knows little about Ukraine and the events taking place in it; the same can be said about Ukrainians.